Factors influencing nurses’ work engagement: A literature review - Upi Parida (Indonesian Journal of Health Services, 2026)
Background: Nurses’ work engagement is an important component of nursing workforce sustainability because it reflects nurses’ energy, dedication, and involvement in professional practice. Evidence on factors influencing nurses’ work engagement remains diverse across healthcare settings. Objective: This literature review aimed to identify and synthesize factors influencing nurses’ work engagement based on published scientific evidence. Methods: This study used a literature review. Literature searches were conducted through EBSCO, ProQuest, and Google Scholar using combinations of keywords, including “nurse,” “nurses,” “work engagement,” “determinants,” “factors,” “predictors,” “associated factors,” and “work environment.” The inclusion criteria were peer-reviewed articles published from 2020 to 2025, written in English, available in full text, focused on nurses as respondents, and examined work engagement as a main variable or outcome. The exclusion criteria were non-full-text articles, non-peer-reviewed publications, irrelevant titles or abstracts, and studies that did not directly discuss nurses’ work engagement. A total 10 articles were included in the final review. The data were extracted into a structured table and synthesized narratively. Results: The review identified organizational support, working conditions, coworker support, job demands, job resources, job control, work-life balance, burnout, perceived overqualification, stress, and professional commitment as factors influencing nurses’ work engagement. The findings also showed that higher work engagement was associated with increased job satisfaction, better quality of care, stronger critical thinking, improved retention, and lower turnover intention. Conclusion: Nurses’ work engagement is shaped by organizational, job-related, social, and individual factors. Healthcare institutions should strengthen supportive leadership, improve work environments, provide adequate job resources, reduce burnout, and support nurses’ professional development to maintain engagement and improve nursing care quality.